OP0257 Rheumatoid Arthritis-Specific Cardiovascular Risk Calculators Are Not Superior To Risk Calculators Established for The General Population: A Validation Analysis in A Cohort of RA Patients from 7 Countries. (15th July 2016) - Crowson, C.S.; Gabriel, S.E.; Semb, A.G.; van Riel, P.L.; Karpouzas, G.; Dessein, P.H.; Hitchon, C.; Pascual Ramos, V.; Kitas, G.D.; ,
Abstract : Background: Cardiovascular disease (CVD) risk calculators developed for the general population do not accurately predict CVD events in patients with rheumatoid arthritis (RA). Objectives: To externally validate risk calculators recommended for use in patients with RA including the European League Against Rheumatism (EULAR) 1.5 multiplier, the Expanded Cardiovascular Risk Prediction Score for Rheumatoid Arthritis (ERS-RA) and QRISK2. Methods: Seven RA cohorts from United Kingdom, Norway, Netherlands, United States, South Africa, Canada and Mexico were combined. Data on baseline CVD risk factors, RA characteristics and CVD outcomes (including myocardial infarction, ischemic stroke and cardiovascular death) were collected using standardized definitions. Performance of QRISK2, EULAR multiplier and ERS-RA was compared to other risk calculators (ACC/AHA, Framingham Adult Treatment Panel III [FRS-ATP] and Reynolds Risk Score) using c-statistics and net reclassification index (NRI). Results: Among 1796 RA patients without prior CVD (mean age: 54.0 [SD: 14.0] years, 74% female), 100 developed CVD events during a mean follow-up of 6.9 years (12430 person-years). Estimated CVD risk by ERS-RA (mean: 8.8%, SD: 9.8%) was comparable to FRS-ATP (mean: 9.1%, SD:8.3%) and Reynolds (mean: 9.2%, SD: 12.2%), but lower than ACC/AHA (mean: 9.8%, SD: 12.1%) and QRISK2 (mean: 15.5%, SD: 13.9%) estimates. Discrimination was not improved for ERS-RA (c-statistic=0.69), QRISK2 or EULAR multiplier applied to FRS-ATP and ACC/AHA (c-statistic=0.72 for all) compared to ACC/AHA and FRS-ATP (c-statistic=0.72 for both). The NRI for ERS-RA were low (-0.8% vs. ACC/AHA and 2.3% vs. FRS-ATP). The NRI for QRISK2 compared ACC/AHA was low (-2.4%). The NRI for QRISK2 compared to FRS-ATP was higher, but not significant (NRI: 25.0%, 95% CI: -9.4–34.7%). The EULAR multiplier only reclassified 6 patients above the 7.5% treatment threshold for the ACC/AHA calculator and 3 patients above the 20% treatment threshold for the FRS-ATP calculator, so the NRI was negligible. Conclusions: The QRISK2, EULAR multiplier and ERS-RA algorithms did not predict CVD risk more accurately in patients with RA than CVD risk calculators developed for the general population. Acknowledgement: The ATACC-RA consortium: S Gabriel, C Crowson, E Matteson, G Kitas, K Douglas, A Sandoo, AG Semb, S Rollefstad, E Ikdahl, T Kvien, P Van Riel, E Arts, J Fransen, S Rantapää-Dahlqvist, S Wållberg-Jonsson, L Innala, G Karpouzas, P Sfikakis, E Zampeli, P Dessein, L Tsang, MA Gonzalez-Gay, A Corrales, H El-Gabalawy, C Hitchon, V Pascual Ramos, I Contreras Yáñez, M van de Laar, H Vonkeman, I Meek, E Husni, R Overman, I Colunga, D Galarza Disclosure of Interest: None declared